Culture-Based Landscape Concept of the Sea Tribe Old Kampong of Batam City - CHANET, Nabila Tamaya; GUNAWAN, Andi; MUNANDAR, Aris (Journal of Environmental Management and Tourism, 2022)
Sea tribes is one of the native tribes still surviving in Batam city despite its rapid development. Their life patterns had changed from when they lived in the sea until now, living on the island's shores. In addition, these changes reflect how they currently use space for their daily lives. The current condition of the settlement arrangement still does not accommodate the principles of their way of life, who constantly sail the ocean. In light of this, research is needed to formulate a residential landscape that accommodates their cultural needs. This study aims to formulate the model of the sea tribe’s landscape concept based on their culture. This study uses a descriptive method based on field observations and interviews with traditional leaders and experts in the field of the Sea Tribe. The spatial concept of the entire landscape is in the form of a circle with a radial pattern consisting of a reception area, residential space, public open space, and conservation space. This concept is based on the way of life of the local community. The local community carries out the interaction between areas in their daily life. The settlement pattern is linear along the island's coast by making the sea the front yard and outward oriented.